Analisis Alokasi Anggaran Pendidikan Secara Makro Serta Relevansinya Terhadap Capaian Human Development Index Pada Dimensi Pendidikan - Siti Sanisah; Nur Kumala Dewi; Edi Edi; Nurin Rochayati (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2023)
The education budget is a support system for achieving educational goals which lead to improving the quality of human resources, one of which can be represented through HDI achievements in the education dimension. This mixed method research with the exploratory sequential design aims to conduct an in-depth study of the relevance of the education budget in three regions in the West Nusa Tenggara region (East Lombok, Central Lombok, and Mataram) towards HDI achievements in the education dimension. The research data were obtained from documentation studies, focused synthesis, and responses to questionnaires, analyzed with a qualitative approach and followed by quantitative analysis. The results showed that the relevance of the education budget to HDI achievement in the education dimension was in the less category (East and Central Lombok) and irrelevant (Mataram). It is suggested that educational planners can adjust budget planning with the grand design of education development, increase the proportion of direct spending on education, and be creative and innovative in implementing educational programs and activities. Keywords: Education badget; relevance; human development index.